THE ANALYSIS OF THE PRESENT SITUATION OF CHINESE STUDENT’S MENTAL HEALTH PROBLEMS: THE CASE STUDY OF FOUR CHINESE’S UNIVERSITIES - Qing, Li (Journal of Social Science and Cultural, 2023)
This research aims to analyze the psychological health problems of Chinese college students during the Covid-19 epidemic from four universities located in northern, central, western, and southern of China; and proposes teaching methods for students’ mental health to strengthen the environmental system for solving mental health problems and make recommendations to university administrators to address students’ mental health issues most effectively. The target group of the study was students from grades 1-4 in four public universities, with a target group of 122,344 people. The researchers collected 118,684 online questionnaires, accounting for 99.45% of all questionnaires. Then organize the data through Microsoft Excel programs and analyze the statistical data through SPSS Python and HiveSQL tools, classify the required issues into target groups, and then classify the concept of mental health issues into level 1 serious mental problems, level 2 mental problems, and level 3 mental problems. The problem of job stress among students is considered the most serious, followed by the pressure of studying and adapting to universities. Based on the results of the above study, the researchers recommend appointing a mental health expert as a consultant. Or have a mentor observe the symptoms of students and provide good advice on their psychological state. Or have a friend help. The counselor must have a face-to-face conversation with the student. If any abnormality occurs, the parent should be notified immediately. Collect the students’ information for further intervention and treatment. Ministry of Mental Health Education.